Maximum Ride : the manga. 6 - Lee, NaRae; Patterson, James, 1947-; Patterson, James, 1947- (London : Arrow Books, 2013)
There is a rift in the flock and everyone must choose to follow Max and her team to Europe, or Fang and his crew as they head west.
Based on: Maximum ride / James Patterson.
Young Adult.
Young Adult
Keywords: Patterson, James, -- 1947- -- Adaptations -- Juvenile literature; Patterson, James, -- 1947- -- Adaptations; Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc -- Juvenile fiction; Good and evil -- Comic books, strips, etc -- Juvenile fiction; Scientists -- Comic books, strips, etc -- Juvenile fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Genetic engineering -- Fiction; Good and evil -- Fiction; Science fiction; Scientists -- Fiction; Adventure graphic novels; Comic books, strips, etc; Genetic engineering -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Manga; Science fiction graphic novels; Scientists -- Comic books, strips, etc -- Fiction; Adventure fiction; Graphic novels; Science fiction comic books, strips, etc